HIGH HUMAN FEELINGS IN EARLY ADOLESCENCE IMPACT ON CAREER CHOICE (American Journal of Interdisciplinary Research and Development, 2022)
One of the particularly noteworthy periods in personality development is early adolescence, which includes young people aged 15-18. The significant feature of this period is the improvement and self-expression of the "I". In this period, it is also manifested in the desire of young people to show their independence as a result of obtaining passports and having the opportunity to participate in elections.